Pengaruh Efikasi Diri dan Sosial Ekonomi Keluarga terhadap Minat Melanjutkan Studi ke Perguruan Tinggi melalui Orientasi Masa Depan pada Siswa SMA Negeri Jakarta Barat - Nizmah Fajar Riyanti; Riswandi Riswandi; Aditya Pratama (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to examine and analyze the influence of self-efficacy and family socioeconomic status on students' interest in pursuing higher education, both directly and through future orientation as a mediating variable, among students of public senior high schools in West Jakarta. This research employed an explanatory quantitative approach using a survey method. The population comprised all eleventh-grade social science students at SMA Negeri 16 Jakarta, SMA Negeri 57 Jakarta, and SMA Negeri 101 Jakarta, totaling 360 students, with a sample of 190 respondents determined through proportionate stratified random sampling. Data were collected using a Likert-scale questionnaire distributed online via Google Form and analyzed using Partial Least Square Structural Equation Modeling (PLS-SEM) with SmartPLS version 4.1.1.8. The results show that self-efficacy, family socioeconomic status, and future orientation each have a positive and significant effect on students' interest in pursuing higher education. In addition, self-efficacy and family socioeconomic status are also found to have a positive and significant effect on future orientation. Furthermore, future orientation is proven to positively and significantly mediate the effect of both self-efficacy and family socioeconomic status on students' interest in pursuing higher education. These findings reinforce the Theory of Planned Behavior, Bandura's Social Cognitive Theory, and Future Time Orientation theory in explaining the process by which students' interest in continuing their education to the higher education level is formed.